Early muscle recovery following robotic-assisted unicompartmental knee arthroplasty - Emma Moon; Paul Gaston; James T. Patton; Allison Bell; Philip M Simpson; Gavin J MacPherson; David F. Hamilton (BMC Research Notes, 2023)
Abstract Background Robotic-assisted unicompartmental knee arthroplasty (UKA) improves implant accuracy, however whether this translates to patient function is less clear. Various outcomes have been reported but muscle recovery has not been previously investigated. Objective To explore sequential change in lower limb muscle strength following robotic-assisted UKA with isokinetic dynamometry. Results 12 participants undergoing rUKA for medial compartment osteoarthritis were assessed pre-operatively, and at 6- and 12-weeks post-operatively. Maximal muscle strength changed over time in both quadriceps (p = 0.006) and hamstrings (p = 0.018) muscle groups. Quadriceps strength reduced from 88.52(39.86)Nm to 74.47(27.58)Nm by 6-weeks (p = 0.026), and then recovered to 90.41(38.76)Nm by 12-weeks (p = 0.018). Hamstring strength reduced from 62.45(23.18)Nm to 54.12(20.49)Nm by 6-weeks (p = 0.016), and then recovered to 55.07(17.99)Nm by 12-weeks (p = 0.028). By 12-weeks quadriceps strength was 70% and hamstrings 83% of the values achieved in the un-operated limb. Substantial improvement was seen in all other measures over time, with sequential positive change in Timed-up-and-go test (p = 0.015), 10 m walk test (p = 0.021), range of knee flexion (p = 0.016) and PROMs (p < 0.025).